Integrated services digital network digital signalling system no. 1 (DSS1), network layer, user-network management / Al-Imran Mohammad Amin and Ibrahim Abd Rahman - Mohammad Amin, Al-Imran; Abd Rahman, Ibrahim (1992)
This Industrial project was done during the four months at Syarikat Telekom Malaysia Berhad. The purpose of this project is to study layer 3 protocol which is called Digital Subscriber Signalling System No.1 (DSS1) which will enable Telekom Malaysia to standardize the options offered by the different vendors.